2023
DOI: 10.1590/2675-2824071.22047vfp
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of polycyclic aromatic hydrocarbons in Santos Bay (Brazil) and its adjacent continental shelf

Abstract: This study evaluated the bioavailability of polycyclic aromatic hydrocarbons (PAHs) in Santos Bay (SB) and the adjacent Santos Continental Shelf (SCS) in Brazil. Biliary metabolites were measured in several fish species to establish a baseline for future monitoring programs. Bile samples from different species of fish were collected monthly from July to December 2005 in SB, and in August 2005 and February 2006 on SCS. Metabolite concentrations were determined using high-performance liquid chromatography with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Heterotrophic bacteria dominated the picoplankton community throughout the study period and among other photosynthetic counterparts, Synechococcus showed greater relative importance than picoeukaryotes. Patire et al (2023) measured biliary metabolites in various fish species, establishing a baseline for future monitoring programs aimed at evaluating the bioavailability of Polycyclic Aromatic Hydrocarbons (PAHs). These authors presented a study carried out in Santos Bay (SB) and the adjacent Santos Continental Shelf (SCS), Brazil.…”
Section: Ocean and Coastal Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotrophic bacteria dominated the picoplankton community throughout the study period and among other photosynthetic counterparts, Synechococcus showed greater relative importance than picoeukaryotes. Patire et al (2023) measured biliary metabolites in various fish species, establishing a baseline for future monitoring programs aimed at evaluating the bioavailability of Polycyclic Aromatic Hydrocarbons (PAHs). These authors presented a study carried out in Santos Bay (SB) and the adjacent Santos Continental Shelf (SCS), Brazil.…”
Section: Ocean and Coastal Researchmentioning
confidence: 99%
“…Despite their high concentrations, the levels of the naphthalene metabolite were in regions of low contamination, while those of the benzo[a]pyrene metabolite were in the same range as those reported in moderately contaminated areas, which may indicate pyrolytic contamination by PAHs. The metabolite data presented by Patire et al (2023) are important baseline information for the study region, which is highly urbanized and home to several sources of contaminants. Nunes et al (2023) studied the spread of the largest oil spill accident that happened off the Brazilian coast from August 2019 to March 2020.…”
Section: Ocean and Coastal Researchmentioning
confidence: 99%